2009
DOI: 10.1080/00207390802642229
|View full text |Cite
|
Sign up to set email alerts
|

Students’ experiences with mathematics teaching and learning: listening to unheard voices

Abstract: This study documents students' views about the nature of mathematics, the mathematics learning process and factors within the classroom that are perceived to impact upon the learning of mathematics. The participants were senior secondary school students. Qualitative and quantitative methods were used to understand the students' views about their experiences with mathematics learning and mathematics classroom environment. Interviews of students and mathematics lesson observations were analysed to understand how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…which are seen to be correlated with the feelings of disaffection, failure and loss of interest in learning mathematics (Zan et al, 2006). Therefore, the literature regarding learners' mathematics-related beliefs includes a large spectrum of studies exploring their beliefs about topics such as -the nature of mathematics (Young-Loveridge et al, 2006), attitude towards learning mathematics (Grootenboer & Marshman, 2016), self-efficacy (Kele & Sharma, 2014), mathematics teaching (Mapolelo, 2009), the use-value of mathematics (Kollosche, 2017;Onion, 2004;Pais, 2013), their mathematical identities (Andersson et al, 2015;Bishop, 2012), emotional disaffection (Nardi & Steward, 2003), anxiety (Young et al, 2012) towards mathematics; and more.…”
Section: Learners' Beliefs and Mathematics Education Researchmentioning
confidence: 99%
“…which are seen to be correlated with the feelings of disaffection, failure and loss of interest in learning mathematics (Zan et al, 2006). Therefore, the literature regarding learners' mathematics-related beliefs includes a large spectrum of studies exploring their beliefs about topics such as -the nature of mathematics (Young-Loveridge et al, 2006), attitude towards learning mathematics (Grootenboer & Marshman, 2016), self-efficacy (Kele & Sharma, 2014), mathematics teaching (Mapolelo, 2009), the use-value of mathematics (Kollosche, 2017;Onion, 2004;Pais, 2013), their mathematical identities (Andersson et al, 2015;Bishop, 2012), emotional disaffection (Nardi & Steward, 2003), anxiety (Young et al, 2012) towards mathematics; and more.…”
Section: Learners' Beliefs and Mathematics Education Researchmentioning
confidence: 99%
“…For example, Mapolelo conducted a research on beliefs about the nature of mathematics, mathematics learning and factors that impact on learning mathematics in three rural senior secondary schools in Botswana [2]. Finding revealed that students feel learning by memorization determines their success in solving problems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As Mapolelo these beliefs may pose difficulties for teachers who may hold constructivist views of mathematics and want to teach mathematics in a constructivist manner. Because, the views that students hold on how mathematics problems are solved and on the number of solutions to the mathematics problems are an important component in the culture of the mathematics classroom, since it is linked with the way mathematics is taught and received [2].…”
Section: The Nature Of Students' Beliefs About Mathematics Learning Amentioning
confidence: 99%
See 2 more Smart Citations